Kidney transplant: graft and recipient profiling - O'Dair, Jonathan David (2009)
Despite the recent introduction of a number of new and more potent anti-rejection drugs, the incidence of rejection and long-term graft survival remain unchanged. There remains a significant difference in long-term graft survival depending on the source of the donor. The purpose of this study was to examine gene expression in the transplanted kidney using microarray technology to identify potential biomarkers that could be used to predict and monitor graft function so that appropriate interventions could be made in the event of graft dysfunction.